Service Strategy for Higher Education Service Institutions Region XVI Gorontalo - Laliyo, Surajuddin; Usu, Idrus; Yakup, Yakup; Karundeng, Deby R. (LPPPIPublishing, 2023)
The research objective was to determine the role of the XVI Gorontalo Higher Education Service Institutions in implementing service strategies for improving the management quality of private tertiary institutions, especially in terms of internal and external service strategies and managerial roles in improving the quality management performance of private tertiary institutions within the XVI region Higher Education Service Institutions. Gorontalo. The analytical method uses a technical SWOT analysis. The results of the study show that the Higher Education Service Institution (LLDIKTI) as a facilitator through its services can bring together various supporting interests. Education, Student and Academic Staff, Research and Community Service and Other Supporting Programs that put quality demonstrations that intersect with the interests of the business world and industry through the Merdeka Belajar program and the independent campus.